First Aid Practices for Injured Children in Rural Ghana: A Cluster-Random Population-Based Survey. Issue 1 (1st February 2021) - Gyedu, Adam; Stewart, Barclay; Otupiri, Easmon; Donkor, Peter; Mock, Charles
Abstract: Introduction: The majority of injury deaths occur outside health facilities. However, many low- and middle-income countries (LMICs) continue to lack efficient Emergency Medical Services (EMS). Understanding current first aid practices and perceptions among members of the community is vital to strengthening non-EMS, community-based prehospital care. Study Objective: This study sought to determine caregiver first aid practices and care-seeking behavior for common household child injuries in rural communities in Ghana to inform context-specific interventions to improve prehospital care in LMICs. Methods: A cluster-randomized, population-based household survey of caregivers of children under five years in a rural sub-district (Amakom) in Ghana was conducted. Caregivers were asked about their practices and care-seeking behaviors should children sustain injuries at home. Common injuries of interest were burns, laceration, choking, and fractures. Multiple responses were permitted and reported practices were categorized as: recommended, low-risk, or potentially harmful to the child. Logistic regression was used to examine the association between caregiver characteristics and first aid practices. Results: Three hundred and fifty-seven individuals were sampled, representing 5, 634 caregivers in Amakom. Mean age was 33 years. Most (79%) were mothers to the children; 68% had only completed basic education. Most caregivers (64%-99%) would employ recommended first aid practices to manage common injuries, such as running cool water over a burn injury or tying a bleeding laceration with a piece of cloth. Nonetheless, seven percent to 56% would also employ practices which were potentially harmful to the child, such as attempting manual removal of a choking object or treating fractures at home without taking the child to a health facility. Reporting only recommended practices ranged from zero percent (burns) to 93% (choking). Reporting only potentially harmful practices ranged from zero percent (burns) to 20% (fractures). Univariate regression analysis did not reveal consistent associations between various caregiver characteristics and the employment of recommended only or potentially harmful only first aid practices. Conclusions: Caregivers in rural Ghanaian communities reported using some recommended first aid practices for common household injuries in children. However, they also employed many potentially harmful practices. This study highlights the need to increase context-appropriate, community-targeted first aid training programs for rural community populations of LMICs. This is important as the home-based care provided for injured children in these communities might be the only care they receive.